Rekrutmen Calon Anggota Legislatif Perempuan Partai Demokrat dan Partai Nasdem Tahun 2014 - IRA AFRIANTY (Universitas Sumatera Utara, 2015)
Political recruitment is one of the substantial indicators to run the functions of political party such as accumulating and aggregating of political interests. The absence of recruitment process can be clearly explained the generation of the party will be loosed. This is the study of recruit-ment pattern of Demokrat Party and Nasional Demokrat Party (Nasdem) in the 2014 election. It focus on how the cadre employment system of both Demokrat party and Nasdem Party in the Province of North Sumatra, especially in recruiting of the women candidates as the parties member. The findings of the study are both political parties have used the open recruitment sys-tem. Then, there are several important points to be highlighted as the process of political re-cruitment. First is the compartmentalization; second is a partisan; third is an immediate surviv-al; and fourth is the civil-service reform. The used method is the descriptive-qualitative method. It intends to describe the results of the study, which are more detail and comprehensive.Keywords: Recruitment, elections, candidates legislative women.